2021
DOI: 10.12998/wjcc.v9.i3.573
|View full text |Cite
|
Sign up to set email alerts
|

Fascial space odontogenic infections: Ultrasonography as an alternative to magnetic resonance imaging

Abstract: BACKGROUND The introduction of modern diagnostic tools has transformed the field of maxillofacial radiology. Odontogenic infection and fascial space involvement have been evaluated with many diagnostic tools, including ultrasonography (USG) and magnetic resonance imaging (MRI). AIM To explore USG as an alternative model to MRI in the detection of fascial space spread of odontogenic infections. METHODS Among 20 patients, 50 fascial spaces were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Semelhante ao espaço mastigatório, o envolvimento do espaço submandibular leva a sintomas graves como trismo, rigidez do pescoço, desconforto respiratório, disfagia, sialorreia e disfonia. Em relação ao envolvimento do espaço facial, encontramos que 65% dos pacientes apresentavam infecção de dois ou mais espaços contra 47% da literatura, 35% dos pacientes apresentaram infecções de espaço único, enquanto a literatura cita uma média de 53% para infecções de um único espaço (Bali, R. K. et al, 2015;Ghali et al, 2021;Yang et al, 2015).…”
Section: Resultsunclassified
“…Semelhante ao espaço mastigatório, o envolvimento do espaço submandibular leva a sintomas graves como trismo, rigidez do pescoço, desconforto respiratório, disfagia, sialorreia e disfonia. Em relação ao envolvimento do espaço facial, encontramos que 65% dos pacientes apresentavam infecção de dois ou mais espaços contra 47% da literatura, 35% dos pacientes apresentaram infecções de espaço único, enquanto a literatura cita uma média de 53% para infecções de um único espaço (Bali, R. K. et al, 2015;Ghali et al, 2021;Yang et al, 2015).…”
Section: Resultsunclassified
“…According to the study by Babu et al [ 23 ], CT was superior to MRI in the aspects of detection of intralesional gas and calcium and motion artifacts. The drawbacks of MRI are obvious as being time-consuming, expensive, and not readily available, making it impractical for most typical cervicofacial space infections [ 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…They conducted a study on 50 patients with superficial fascial spaces, in which US helped in identifying abscesses in 22 patients and cellulitis in 28 patients. However, US could not accurately detect those infections involving deep fascial spaces [ 25 , 27 ], thereby limiting its use in cervicofacial space infections. The study by Kalmovich et al [ 24 ] reported that ultrasound did not correlate well with the presence of parapharengeal abscess.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible sources of infection include trauma, sinus disease, and invasive treatment of the orofacial area [ 3 ]. Common symptoms of fascial space infection and abscess in the orofacial area include limited mouth opening, neck stiffness, dyspnea, dysphagia, fever, swelling and redness [ 4 ]. If the diagnosis and treatments of fascial space abscess in the orofacial area are delayed, the abscess can spread into more critical structures including neck, airway, orbital septum, and even brain, leading to grave consequences [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%